IT application tools in business - Maata, Rolou Lyn Rodriguez; Caoili-Tayuan, Ronina (Quezon City, Philippines : C & E Publishing Inc., 2021)
IT Application Tools in Business introduces the basic concepts of information technology (IT) applications, tools, and techniques in business environments. It is skillfully arranged to facilitate students' learning and acquisition of technical and applied skills. Hence, it is divided into six units comprised of comprehensive discussionof the following topics: (1) information technology in a business environment, (2) introduction to information systems, (3) emerging technologies for business processes, (4) e-business, e-commerce, and m-commerce, (5) functional and enterprise system, and (6) IT governance, ethical, and security issues in IT. Furthermore, it includes real-world scenarios, case studies, and practical exercises to assess students' level of understanding of the topics. With the book's design, students are allowed the opportunities to evaluate existing systems used by business organization, thereby giving them useful knowledge that they can use in their future profession.
Unit 1. Information Technology in a business environment -- Unit 2. Introduction to Information systems -- Unit. 3 Emerging technologies for business processes -- Unit 4. E-Business, E-Commerce and M-Commerce -- Unit 5. Functional and Enterprise Systems -- Unit 6. IT Governance, Ethical and Security Issues in Information technology.
Includes bibliographical references.
Keywords: INFORMATION TECHNOLOGY -- MANAGEMENT